Apical Root Resorption of Endodontically Treated Teeth after Orthodontic Treatment: A Split-mouth Study - Elif Dilara Şeker; Asiye Nur Dinçer; Nihal Kaya (Galenos Yayinevi, 2023)
Objective:The influence of pulp status on orthodontically induced root resorption has attracted attention. The purpose of this study was to compare orthodontically induced root resorption in endodontically treated teeth and their contralateral vital teeth in a split-mouth design.Methods:The sample included 173 patients who had at least one endodontically treated tooth, and their vital contralateral teeth served as the control group before the completion of orthodontic treatment. Apical root resorption measurements were performed by the comparison of digital panoramic X-ray images obtained at the beginning and at the end of the orthodontic treatment. Kruskal-Wallis, Mann-Whitney U, and Wilcoxon tests were used for statistical analysis.Results:There was no statistically significant difference in apical root resorption between the endodontically treated teeth and the contralateral teeth (p>0.05). Sex and tooth type had no effect on apical root resorption both in the endodontically treated teeth and the contralateral vital teeth (p>0.05). Orthodontic treatment with extraction caused more apical root resorption in the vital teeth than in the endodontically treated teeth (p<0.05). The quality of the endodontic treatment had no significant influence on apical root resorption (p>0.05).Conclusion:Endodontic treatment does not produce greater apical root resorption compared with the vital teeth.